Do China’s low-carbon technology products and environmental goods trade mitigate energy-related carbon emissions in Africa? - Dinkneh Gebre Borojo; Jiang Yushi (PLoS ONE, 2026)
Motivated by the rise in green trade between China and Africa and the growing environmental pressures associated with energy-related emissions in Africa, this study examines the impacts of low-carbon technology (LT) products and environmental goods (EGs) imported from China on the energy-related carbon emissions intensity (CEI) of 42 African countries for the period 2003–2023. To account for endogeneity issues and distributional differences, the study employs instrumental variables and panel quantile techniques. The findings reveal several important points. First, LT products and EGs imported from China significantly reduce the energy-related CEI of African countries. Second, the influence of imports of LT products and EGs on energy-related CEI varies by income level: they increase energy-related CEI in low-income African economies but decrease it in middle-income African nations. Third, the import of LT products and EGs has a stronger energy-related CEI-reducing effect in African countries with better institutional frameworks. These findings contribute to the current literature by offering a detailed and nuanced understanding of how trade in LT products and EGs can help reduce energy-related carbon emissions. Policy recommendations are presented based on these findings.